2020
DOI: 10.3390/ijerph17082758
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perception of Periodontal Health and Associated Factors: A Cross-Sectional Population-Based Study

Abstract: The aim of this cross-sectional study was to explore sociodemographic, behavioral, and clinical factors associated with self-awareness of periodontal health. Data were collected from a representative sample of 736 adults (25-75 years old) in a city of Northern Italy who self-assessed gingival bleeding, oral malodor, and tooth mobility in a questionnaire and who underwent clinical periodontal examination and organoleptic evaluation. Approximately 50% of the subjects were aware of their actual gingival health st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 77 publications
(135 reference statements)
3
30
0
8
Order By: Relevance
“…Previous epidemiological studies have demonstrated the age dependence and gender differences of gingival bleeding data [ 8 , 9 , 28 , 30 ]. Our results found a higher prevalence of GB among females and are in line with those of other studies [ 8 , 28 , 31 ]. The higher SRGB prevalence observed in females could be attributed to the facts that (i) women are more aware of their oral health and (ii) women are more susceptible to gingival inflammation exacerbations due to hormonal fluctuations [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous epidemiological studies have demonstrated the age dependence and gender differences of gingival bleeding data [ 8 , 9 , 28 , 30 ]. Our results found a higher prevalence of GB among females and are in line with those of other studies [ 8 , 28 , 31 ]. The higher SRGB prevalence observed in females could be attributed to the facts that (i) women are more aware of their oral health and (ii) women are more susceptible to gingival inflammation exacerbations due to hormonal fluctuations [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, Buhlin et al observed an inverse association of SRGB according to age [ 34 ]. Elderly people have a higher number of missing teeth than those younger, but most importantly, they seem to be less aware of their gingival bleeding, as shown in the study of Romano et al [ 31 ]. Ebersole et al demonstrated the presence of age-associated alterations in innate immune function within the periodontium, which could affect not only the initiation but also the resolution of inflammation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gingival bleeding is an indicator of the presence of an inflammatory lesion. Gingival bleeding is objective 35 , and therefore, may be less confusing than other items, such…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the predictive ability varied with the definition used for periodontitis. Generally, periodontitis progresses silently, and the pathological changes take a long time before pain, discomfort, and functional disability occur 35 . This poor self-perception of periodontitis progression can partly explain the lower predictive ability of the self-report in milder cases of periodontitis in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation